2016
DOI: 10.1063/1.4960201
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the stability of both the structure and velocity of domain walls in magnetic nanowires

Abstract: Citation for published item:fr nd£ oD tF nd etkinsonD hF @PHITA 9gontrolling the st ility of oth the stru ture nd velo ity of dom in w lls in m gneti n nowiresF9D epplied physi s lettersFD IHW @TAF HTPRHSF Further information on publisher's website: PHIT emeri n snstitute of hysi sF his rti le m y e downlo ded for person l use onlyF eny other use requires prior permission of the uthor nd the emeri n snstitute of hysi sF he following rti le ppe red in fr nd£ oD tF etkinsonD hF @PHITAF gontrolling the st ility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Various wire geometries were studied to obtain a generalised understanding of the influence of the Pt layer. Parallel-sided and fixed-angle periodic triangular featured nanowires were fabricated to provide modulation that is known to influence the DW propagation 25 . The parallel-sided nanowire has a width of 250 nm.…”
Section: Experimental and Micromagnetic Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various wire geometries were studied to obtain a generalised understanding of the influence of the Pt layer. Parallel-sided and fixed-angle periodic triangular featured nanowires were fabricated to provide modulation that is known to influence the DW propagation 25 . The parallel-sided nanowire has a width of 250 nm.…”
Section: Experimental and Micromagnetic Simulation Detailsmentioning
confidence: 99%
“…However, although the mechanisms occurring at the NM/FM interface have been explored in magnetic wires with strong IDMI and perpendicular anisotropy, few studies have addressed the influence of the heavy metal layer on in-plane magnetization processes and in nanowires 21 , 22 . Furthermore, whilst it is known from experimental and micromagnetic studies of in-plane magnetic nanowires that the field driven DW propagation behaviour is controlled by precessional processes that leads to Walker breakdown 23 , and which in turn can be controlled by periodic structuring of the nanowires 24 , 25 , the influence of additional interfacial damping and IDMI on the domain wall behaviour has not been studied in detail. Understanding the influences of both enhanced damping and IDMI on the DW dynamic behaviour relates to a fundamental physical understanding and is relevant to technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…structural defects and inhomogeneous alloy components introduced in the fabrication [29,30]. Edge modulation and notches can improve the deterministic control [31][32][33]. Nevertheless, the randomness still exists and the resulting local barriers of notches are not ideally identical.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the obtained data, we can work out the role of edge defects in the long edges of those studied NWs by adding the obtained data into the wall phase diagram. In fact, many researchers showed that edge behaviors strongly induce the degree of asymmetry in a TDW/VDW [17][18][19]. Understanding this factor leads us to work out a quantitative change if a TDW is created in a straight or curved NW.…”
Section: Introductionmentioning
confidence: 99%